The Influence of the Application and Understanding of SAK EMKM-Based Accounting on the Financial Statements of UMKM Pempek in Palembang City - Ira Syafira; Leriza Desitama Anggraini; Andini Utari Putri (International Journal of Community Service & Engagement, 2023)
This study aims to analyze the influence of the application and understanding of accounting based on SAK EMKM on the financial statements of Small and Medium Enterprise. The data sources were primary data and data collection techniques were observation and questionnaires filled out by 50 units of Small and Medium Enterprise. The data were processed using multiple linear regression analysis. The application and understanding of SAK EMKM-based accounting have a positive effect on financial statement variables.